The interaction between two parametric excitations of the second and third degrees - Dao, Nguyen Van (Vietnam Journal of Mechanics, 2000)
The interaction between nonlinear oscillations is an interesting problem which has attracted many researches. The interaction between forced and parametric excitations and between two parametric excitations of first and second degrees and first and third degrees, is informed in [1]. In the present paper, we study interaction between two parametric excitations of the second and third degrees. The asymptotic method of nonlinear mechanics in combination with a computer is used.